Faktor-Faktor Yang Mempengaruhi Kecenderungan Fraud Akuntansi di Pemerintahan Desa - Muhammad Syaiful Anwar; Sri Trisnaningsih (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
Accounting fraud is a serious problem that has occurred in both the business and public sectors from the past to the present. Accounting fraud is closely related to fraudulent practices. Since 2015, the central governmnet has allocated funds intended for villages and distributed them to all villages as an effort to improve community welfare and reduce poverty levels. However, in its implementation, there are still varios cases of misappropriation of village funds committed by village officials. Based on this condition, this study aims to examine and determine whether there is an effect of internal control effectivennes, organizational ethical culture, and individual morality on the tendency of accounting fraud. This study uses a quantitative approach with a sampling technique in the form of a census or total sampling method. Primary data were used in this study, obtained through the distribution of online questionnaires. The number of respondents in this study was 48 people, consisting of village heads, village secretaries, and heads of financial affairs of village governments in Wringinanom District, Gresik Regency. The data analysis technique used was multiple linear regression analysis. The partial result show that the internal control effectivennes variable has a significance value of 0,000 < 0,05 and a regression coefficient of -0,517, the organizational ethical culture variable has a significance value of 0,000 < 0,05 and a regression coefficient of -0,634, and the individual morality variable has a significance value of 0,000 < 0,05 and a regression coefficient of -0,770, this means that all independent variables in this study have a negative effect on the tendency of accounting fraud. Simultaneously, the significance value obtained is 0,000 < 0,05, indicating that internal control effectiveness, organizational ethical culture, and individual morality simultaneously have an effect on the endency of accounting fraud.